Selection of risk factors to be included in the Canadian Food Inspection Agency risk assessment inspection model for food establishments. (October 2018) - Zanabria, Romina; Racicot, Manon; Cormier, Mathieu; Arsenault, Julie; Ferrouillet, Cécile; Letellier, Ann; Tiwari, Ashwani; Mackay, Anna; Griffiths, Mansel; Holley, Rick; Gill, Tom; Charlebois, Sylvain; et al.
Abstract: The Canadian Food Inspection Agency (CFIA) is developing a risk assessment model for food establishments. Previous research on the significance of food safety risk factors determined by literature review and expert advice served as the bases for the current study, to further refine, discriminate and select the most important criteria to be included in the model. This process considered the availability of data sources, the clarity and measurability of the selected factors, undertook the elimination of lower-rated risk factors and grouped those with similar focus of attention, enabling the selection of a final list of risk factors for the model. A method of assessment for the remaining factors was then proposed to allow the quantification of individual risk factors within the model. From the 155 risk factors initially identified, 17 consolidated factors were kept and will be considered for the development of the risk assessment model. Highlights: Risk factors influencing food plant inspection performance were assessed and consolidated. Seventeen factors were retained and will be part of the risk assessment model. Defined criteria will ensure objective risk assessment during federal inspections.